Estado actual de la enseñanza del latín y del griego en España y perspectivas de futuro - Alvar Ezquerra, Antonio, 1954- (2003)
On this paper the author explains the current situation of the instruction of the classical languages within the Spanish Secondary Education system after the last educational changes that have been made. The current panorama it is, in fact, very complex and diversified- due to the peculiar structure that the Spanish Nation has with its Autonomies- but we can glimpse a more positive horizons regarding the Latin, Greek and Classical Culture teaching.
Keywords: Enseñanza -- España; Lengua latina; Lengua griega